المسؤولیة الإجتماعیة وعلاقتھا بالأداء الوظیفي لدى أساتذة معھد علوم وتقنیات التربیة البدنیة والریاضیة - سعودي محمد; مخلوفي یوسف; كروم البشیر (My University, 2020)
عنوان الد ا رسة: المسؤولیة الإجتماعیة وعلاقتها بالأداء الوظیفي لدى أساتذة معهد علوم وتقنیات هدف الد ا رسة : یكمن هدف بحثنا هذا في إب ا رز العلاقة بین المسؤولیة الاجتماعیة بالأداء الوظیفي مشكلة الد ا رسة : هل المسؤولیة الاجتماعیة لها علاقة بالأداء الوظیفي لدى أساتذة معهد علوم وتقنیات ویمكن تحدید مشكل البحث في التساؤل التالي : - مستوى المسؤولیة الاجتماعیة لدى الأستاذ الجامعي . - مستوى الأداء الوظیفي لدى أستاذ الجامعي . فرضیات الد ا رسة : - المسؤولیة الإجتماعیة وعلاقتها بالأداء الوظیفي لدى أساتذة معهد علوم وتقنیات - مستوى المسؤولیة الإجتماعیة لدى الاستاذ الجامعي . - مستوى الاداء الوظیفي لدى أستاذ الجامعي . - توجد علاقة ارتباطیة بین المسؤولیة الاجتماعیة و الأداء الوظیفي لدى الأستاذ الجامعي . إج ا رءات الد ا رسة المیدانیة : العینة : وتم اختیار العینة بشكل عشوائي وتمثلت في 20 استاذ جامعي المجال الزمني والمكاني : أجریت الد ا رسة المیدانیة على مستوى معهد علوم وتقنیات الأنشطة البدنیة والریاضیة بجامعة عمار ثلیجي بالأغواط المنهج : اعتمدنا على المنهج الوصفي المسحي وذلك لملائمته لطبیعة البحث الم ا رد عمله أو القیام به . الأدوات المستعملة في الد ا رسة : فقد تم إتباع تقنیة الاستبیان التي تعتبر من أنجع الطرق للحصول على معلومات حول موضوع أو مشكلة أو موقف . ملخص الدراسة النتائج المتوصل إلیها : أثبتت الد ا رسة أن الشعور بالمسؤولیة ثمرة لتصوُّر الإنسان عن دوره في الحیاة، والتعامل مع سنن الله في النفس والمجتمع، والتوازن بین المطالبة بالحقوق والقیام بالواجبات.. وكما طالعنا في صفحات البحث، فإن المسؤولیة هي سر العم ا رن، وعنوان النجاح والفلاح، والسمو والارتقاء، فلا تسمو أمة ویرتفع شأنها بإذن الله في حیاتها إلا بعد الأخذ بالأسباب، وتحمل المسؤولیات الجسام؛ لأن الله قد سن قانوًنا لم یستثنِ منه مؤمًنا ولا كافً ا ر، وهو أنه - سبحانه وتعالى - لا یضیع أجر من أحسن عملا،ً وقد نكَّر - سبحانه وتعالى - العمل لیدل على كل عمل صالح فیه صلاح الأمة والمجتمع، ویا لیته یكون على منهاج رب العالمین، الذي وضع هذا القانون في الأرض، والذي أخذ به - یا للحسرة - غیُر المسلم، فأقام به أمر حیاته، وتخاذل عنه المسلم فتسوَّل قوت یومه. صحة الفرضیات القائلة : - یوجد مستوى المسؤولیة الإجتماعیة لدى الاستاذ الجامعي . - یوجد مستوى الاداء الوظیفي لدى أستاذ الجامعي . - توجد علاقة ارتباطیة بین المسؤولیة الاجتماعیة والاداء الوظیفي لدى الاستاذ الجامعي
Study title: Social responsibility and its relationship to job performance of the Institute of Science and Technology professors Purpose of the study : The aim of this research is to highlight the relationship between social responsibility and job performance Study problem: Is the social responsibility and its relationship to job performance of the Institute of Science and Technology professors? The research problem can be identified in the following question: - The level of social responsibility of the university professor. - The level of job performance for a university professor. Study hypotheses: - Social responsibility and its relationship to job performance of the Institute of Science and Technology professors - The level of social responsibility of the university professor. - The level of job performance for a university professor. - There is a correlation between the social responsibility and job performance of the university professor. Field study procedures: The sample: The sample was randomly chosen and represented at 20 university professors Time and Spatial Field: The field study was conducted at the level of the Institute of Science and Technology The curriculum: We relied on the descriptive survey method, due to its relevance to the nature of the research to be done or done. The tools used in the study: The questionnaire technique, which is considered one of the most effective ways to obtain information about a topic, problem or situation, was followed. The results reached: The study proved that feeling of responsibility is the result of a person’s perception of his role in life, dealing with the Sunnah of God in the soul and society, and the balance between demanding rights and performing duties .. As we have read in the research pages, responsibility is the secret of urbanization, the title of success and prosperity, and transcendence. And the advancement, so that a nation does not transcend and rise, God willing, in its life, except after the introduction of the reasons, and bear great responsibilities; Because God has enacted a law that does not exclude a believer or a disbeliever, which is that - Glory be to Him - He does not waste the reward of those who do good deeds, and He has denied - Glory be to Him - work to denote every good deed in which the goodness of the nation and society, and if only he would follow the path of the Lord of the Worlds, The one who put this law in the land, and who took it - oh sorry - is the Muslim, so he established his life order, and the Muslim neglected him, so he begged for the sustenance of his day. The validity of the hypotheses: There is a level of social responsibility of the university professor. There is a job performance level for a university professor. - There is a correlation between the social responsibility and job performance of the university professor. Conclusions and suggestions: The necessity to work in a spirit of social responsibility. - The need to use and apply the term performance to create tires that can advance the university. Realizing the importance of the university professor or the professor in general is the focus of the educational process